BLOCKCHAIN AS A TECHNOLOGICAL BASIS OF THE DEVELOPMENT OF BANKS - A. Berdyshev (Вестник университета)
Modern information technologies open up new opportunities for the banking sector as well as carry with them unknown challenges for banks. The article reveals the features of block-technology and the possibility of its use by banks, which in the conditions of technological competition with the financial companies will require from them the ability to enhance competitive advantages based on maximizing the positive effect of the strengths and leveling their weaknesses on the basis of the latest technologies.